2022
DOI: 10.1159/000528635
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic Breast Conserving Surgery: Is There a Need for Standardization? Results of a Nationwide Survey

Abstract: Introduction The NABON Breast Cancer Audit showed that more than 70% of the Dutch women undergoing surgery for breast cancer (BC) maintained their breast contour by breast conserving surgery (BCS) or by immediate reconstruction after ablative surgery. The proportion of oncoplastic surgery applied in patients undergoing breast conserving treatment (BCT) remains unknown. The aim of our study was to assess the need for standardization of oncoplastic breast conserving surgery (OPBCS) in an attempt to enable measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Access to a plastic surgeon can further propagate inequality in breast cancer care, thus, the need for continued education and streamlined training of general surgeons, breast surgeons, and plastic surgeons, on the principles and maintained safety of OPS, is paramount for women with breast cancer in the USA. Some studies have suggested standardization of OPS techniques and referral patterns in other countries, however this does not currently exist in the USA ( 13 ). It is anticipated with the continued adoption and recognition of OPS principles, that plastic surgeons will transition to focus on more advanced and complex level II, and volume replacement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Access to a plastic surgeon can further propagate inequality in breast cancer care, thus, the need for continued education and streamlined training of general surgeons, breast surgeons, and plastic surgeons, on the principles and maintained safety of OPS, is paramount for women with breast cancer in the USA. Some studies have suggested standardization of OPS techniques and referral patterns in other countries, however this does not currently exist in the USA ( 13 ). It is anticipated with the continued adoption and recognition of OPS principles, that plastic surgeons will transition to focus on more advanced and complex level II, and volume replacement techniques.…”
Section: Introductionmentioning
confidence: 99%